Young Sexual Minority Males in the United States: Sociodemographic Characteristics And Sexual Attraction, Identity and Behavior. Issue 1 (6th January 2016) - Fasula, Amy M.; Oraka, Emeka; Jeffries, William L.; Carry, Monique; Bañez Ocfemia, M. Cheryl; Balaji, Alexandra B.; Rose, Charles E.; Jayne, Paula E.
Abstract : CONTEXT: HIV incidence is increasing among 13–24‐year‐old U.S. men who have sex with men, yet limited research is available to guide HIV prevention efforts for this population. METHODS: National Survey of Family Growth data collected in 2002, in 2006–2010 and in 2011–2013 from 8, 068 males aged 15–24 were analyzed to describe the population of U.S. young sexual minority males (i.e., males reporting same‐sex attraction, identity or behavior). Correlates of sexual minority classification were assessed in logistic regression models. RESULTS: An estimated 10% of young males, representing a population of 2.1 million, were sexual minorities. Males had an elevated likelihood of being sexual minorities if they were aged 18–19 or 20–24, rather than 15–17 (prevalence ratio, 1.7 for each); belonged to nonblack, non‐Hispanic racial or ethnic minority groups (1.6); had no religious affiliation, rather than considering religion very important (1.9); or lived below the federal poverty level (1.3). They had a reduced likelihood of being sexual minorities if they lived in metropolitan areas outside of central cities (0.7). Among young sexual minority males, 44% were 15–19 years old, 29% were poor and 59% resided outside central cities. Forty‐seven percent had engaged in same‐sex behavior. Of those with data on all measured dimensions of sexuality, 24% reported same‐sex attraction, identity and behavior; 22% considered themselves heterosexual, yet had had a male sex partner. CONCLUSION: Future investigations can further explore subpopulations of young sexual minority males and assess sexual trajectories, resilience and HIV risk.